ВЫЯВЛЕНИЕ ОСОБЕННОСТЕЙ УПРАВЛЕНИЯ ИННОВАЦИОННЫМИ ПРОЦЕССАМИ В РЕГИОНАЛЬНЫХ ВУЗАХ РЕСПУБЛИКИ УЗБЕКИСТАН - Доспанов, Р. (SCIENCE and SOCIETY, 2025)
Our article deals with management of innovation processes in regional universities of Uzbekistan in the context of globalization and the transition to a knowledge economy. The article emphasizes the need for cooperation between universities and industrial enterprises to train highly qualified personnel capable of supporting the innovative development of regions.